Why Catholics rebel: tsarist confessional policy as a catalyst of grassroots opposition in the western borderlands. Issue 1 (2nd January 2022) - Staliūnas, Darius
ABSTRACT: This article asks why the Russian Empire's closure of hundreds of Catholic monasteries, convents, and churches in the early and mid-nineteenth century proceeded without major incidents, while in the 1880s and 1890s it met with grassroots resistance. The article specifically deals with tsarist authorities' closure of the Benedictine convent and church in Kražiai in 1893, which provoked the fierce resistance of parishioners. The Kražiai case grew into a significant symbol that strengthened anti-tsarist feelings among Roman Catholics in Poland and Lithuania, and at the same time it disclosed the presence of larger issues related to the management of the western borderlands. The author argues that, while a number of contingent factors played a specific role in the escalation, on a more structural level it was very difficult for the tsarist state to manage the empire's western borderlands whenever it deflected from a well-coordinated, even if harsh policy of discriminating against the non-Orthodox population. The article also shows how different confessional policy priorities – or at least different approaches to the same policy – emerged among various government institutions and came into conflict.